Increasing trend in the rate of infectious disease hospitalizations among Alaska Native people - Holman, Robert C; Hennessy, Thomas W; Haberling, Dana L; Callinan, Laura S; Singleton, Rosalyn J; Redd, John T; Steiner, Claudia A; Bruce, Michael G
Objectives To examine the epidemiology of infectious disease (ID) hospitalizations among Alaska Native (AN) people Methods Hospitalizations with a first-listed ID diagnosis for American Indians and ANs residing in Alaska during 2001–2009 were selected from the Indian Health Service direct and contract health service inpatient data ID hospitalizations to describe the general US population were selected from the Nationwide Inpatient Sample Annual and average annual (2007–2009) hospitalization rates were calculated Results During 2007–2009, IDs accounted for 20% of hospitalizations among AN people The 2007–2009 average annual age-adjusted ID hospitalization rate (2126/100,000 persons) was higher than that for the general US population (1679/100,000; 95% CI 1639–1720) The ID hospitalization rate for AN people increased from 2001 to 2009 (17%, p<0001) Although the rate during 2001–2009 declined for AN infants (<1 year of age; p=003), they had the highest 2007–2009 average annual rate (15106/100,000), which was 3 times the rate for general US infants (5215/100,000; 95% CI 4783–5647) The annual rates for the age groups 1–4, 5–19, 40–49, 50–59 and 70–79 years increased (p<005) The highest 2007–2009 age-adjusted average annual ID hospitalization rates were in the Yukon-Kuskokwim (YK) (3492/100,000) and Kotzebue (3433/100,000) regions; infant rates were 30422/100,000 and 26698/100,000 in these regions, respectively During 2007–2009, lower respiratory tract infections accounted for 39% of all ID hospitalizations and approximately 50% of ID hospitalizations in YK, Kotzebue and Norton Sound, and 74% of infant ID hospitalizations Conclusions The ID hospitalization rate increased for AN people overall The rate for AN people remained higher than that for the general US population, particularly in infants and in the YK and Kotzebue regions Prevention measures to reduce ID morbidity among AN people should be increased in high-risk regions and for diseases with high hospitalization rates